PENGARUH PENYULUHAN TENTANG SHK DENGAN MEDIAVIDEO TERHADAP KESEDIAAN PEMERIKSAAN SHK PADA BBL DI WILAYAH PUSKESMAS PUGER - Mayantie, Riesma Dwi; Sugijati, Sugijati; Kiswati, Kiswati; Kanarsih, I Gusti Ayu (HEALTHY : Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Congenital Hypothyroidism Screening (CHS) is a government program as an effort to early detect cases of Congenital Hypothyroidism (CH) in newborns for subsequent treatment. In 2023, the coverage reached 6,469 babies out of 49,536 (13.06%) live births in Jember Regency, whereas the SHK target was 100%. Puger Health Center in 2023 covered 33 babies (4%) out of 823 live births. to determine the effect of counseling about SHK using video media on the willingness of SHK examinations in newborns in the Puger Health Center area. The type of research used was comparative. The population of this study consisted of all pregnant women with 38-39 weeks gestation in the Puger Health Center working area totaling 80 respondents and a research sample of 66 respondents. The case control group sampling technique was carried out using proportional stratified random sampling. Shows that respondents who received counseling without video media as many as 20 people (60.6%) agreed to provide willingness to SHK examination on newborns. Meanwhile, respondents who received counseling with video media reached 28 people (84.8%) who stated their willingness to SHK examination on newborns. The results of the chi square test analysis showed a p value of 0.026 where the p value <? = 0.05 means that there is an effect of counseling about SHK with video media on the willingness of SHK examination on newborns in the Puger Health Center area. Counseling about SHK with video media for pregnant women is able to increase understanding, thereby increasing the willingness and achievement of SHK coverage on newborns in the Puger Health Center area. ABSTRAKSkrining Hipotiroidisme Kongenital (SHK) merupakan suatu program pemerintah sebagai upaya menemukan secara dini kasus Hipotiroidisme Kongenital (HK) pada bayi baru lahir untuk kemudian diobati. Pada tahun 2023 capaian cakupan 6.469 bayi dari 49.536 (13,06%) bayi lahir hidup se-Kabupaten Jember padahal target SHK 100%. Puskesmas Puger pada tahun 2023 cakupannya sejumlah 33 bayi (4%) dari 823 bayi lahir hidup. untuk mengetahui pengaruh penyuluhan tentang SHK dengan media video terhadap kesediaan pemeriksaan SHK pada BBL di wilayah Puskesmas Puger. Jenis penelitian yang digunakan adalah komparatif. Populasi penelitian ini terdiri dari seluruh ibu hamil UK 38-39 minggu di wilayah kerja Puskesmas Puger berjumlah 80 responden dan sampel penelitian 66 responden. Teknik pengambilan sampel kelompok case control dilakukan dengan menggunakan teknik proporsional stratified random sampling. Menunjukkan bahwa responden yang mendapatkan penyuluhan tanpa media video sebanyak 20 orang (60,6%) setuju memberikan kesediaan pemeriksaan SHK pada BBL. Sementara itu, responden yang mendapatkan penyuluhan dengan media video mencapai 28 orang (84,8%) yang menyatakan kesediaannya untuk pemeriksaan SHK pada BBL. Hasil analisis uji chi square menunjukkan nilai p adalah 0.026 dimana nilai p < ? = 0,05 artinya terdapat pengaruh penyuluhan tentang SHK dengan media video terhadap kesediaan pemeriksaan SHK pada BBL di wilayah Puskesmas Puger. Penyuluhan tentang SHK dengan media video pada ibu hamil mampu meningkatkan pemahaman, sehingga meningkatkan kesediaan dan capaian cakupan SHK pada BBL di wilayah Puskesmas Puger.